Clinical outcomes of secondary gastroduodenal self‐expandable metallic stent placement by stent‐in‐stent technique for malignant gastric outlet obstruction. Issue 1 (28th August 2014) - Sasaki, Takashi; Isayama, Hiroyuki; Nakai, Yousuke; Takahara, Naminatsu; Hamada, Tsuyoshi; Mizuno, Suguru; Mohri, Dai; Yagioka, Hiroshi; Kogure, Hirofumi; Arizumi, Toshihiko; Togawa, Osamu; Matsubara, Saburo; et al.
<x xml:space="preserve">Abstract</x> Background and Aim To evaluate the efficacy and safety of secondary gastroduodenal stent placement after first stent dysfunction for malignant gastric outlet obstruction. Methods We conducted a retrospective analysis to investigate the efficacy and safety of secondary stent‐in‐stent gastroduodenal stent placement. Results Among 260 patients who had been treated with first gastroduodenal stent placement for malignant gastric outlet obstruction, 29 patients (11.2%) were treated with secondary gastroduodenal stent placement because of first stent dysfunction. Pancreatic cancer was the major primary cancer (55.2%). A WallFlex duodenal stent was the most frequently inserted stent both as a first stent (75.9%) and as a secondary stent (62.1%). There were 22 patients (75.9%) that received gastroduodenal stents at the bending site (supraduodenal angle or infraduodenal angle). Technical and clinical success rates were 100% and 86.2%, respectively. Median eating period was 3.0 months, and median survival time was 3.5 months. As for related complications, gastrointestinal perforation, insufficient stent expansion, tumor ingrowth, tumor overgrowth, and cholangitis were experienced in 13.8% (four cases), 6.9% (two cases), 6.9% (two cases), 3.4% (one case), and 3.4% (one case), respectively. Conclusion Secondary gastroduodenal stent placement might be effective for managing first stent dysfunction in malignant gastric outlet obstruction. However, gastrointestinal perforation was the major complication.